2020
DOI: 10.1101/2020.10.23.351551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell analyses reveal phosphate availability as critical factor for nutrition ofSalmonella entericawithin mammalian host cells

Abstract: Salmonella enterica serovar Typhimurium (STM) is an invasive, facultative intracellular pathogen that resides in a specialized membrane-bound compartment termed Salmonella-containing vacuole (SCV). Essential for survival and proliferation in the SCV is Salmonella pathogenicity island II (SPI2) that encodes a type III secretion system (T3SS). The SPI2-T3SS and the effector translocation maintain SCV integrity and formation of specific tubular membrane compartments, called Salmonella-induced filaments (SIFs). Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Together with our results, we conclude that bacteria in the cytosol have the best access to nutrients of the host cell, allowing fast proliferation. In addition to the factors analyzed in this study, the availability of phosphate and C-sources has to be considered ( Röder and Hensel, 2020 ; Röder and Hensel, 2021 ), as well as xenophagic or pyroptotic host cell responses to cytosolic STM. A large SIF-SCV continuum increases the frequency of fusion with vesicles, and allows the bacteria to replicate in the vacuolar compartment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with our results, we conclude that bacteria in the cytosol have the best access to nutrients of the host cell, allowing fast proliferation. In addition to the factors analyzed in this study, the availability of phosphate and C-sources has to be considered ( Röder and Hensel, 2020 ; Röder and Hensel, 2021 ), as well as xenophagic or pyroptotic host cell responses to cytosolic STM. A large SIF-SCV continuum increases the frequency of fusion with vesicles, and allows the bacteria to replicate in the vacuolar compartment.…”
Section: Discussionmentioning
confidence: 99%
“…As cultural growth leads to continuous reduction of nutrient concentrations, the actual inducing concentration is likely lower for most nutritional factors. For a more detailed calibration, shift experiments with transfer in media with various amounts of nutrients may be considered as performed for analyses of phosphate availability ( Röder and Hensel, 2020 ), or inhibition of bacterial growth. The presence of a second, non-regulated fluorescent protein has been used to identify in the intracellular bacterial population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the long turn‐over of sfGFP did not allow to analyse a potential decrease of stress signals acting on intracellular STM. The addition of tags for degradation, such as the LVA tag (Andersen et al, 1998) is possible and allows generation of dual colour reporters with increased dynamic range (Röder, Felgner, & Hensel, 2021; Röder & Hensel, 2021). We observed that induction of all reporters in intracellular STM was higher compared to in vitro exposure to defined stressors.…”
Section: Discussionmentioning
confidence: 99%
“…As cultural growth leads to continuous reduction of nutrient concentrations, the actual inducing concentration is likely lower for most nutritional factors. For a more detailed calibration, shift experiments with transfer in media with various amounts of nutrients be considered as performed for analyses of phosphate availability (Röder and Hensel, 2020b), or inhibition of bacterial growth. The presence of a second, non-regulated fluorescent protein has been used to identify in the intracellular bacterial population.…”
Section: Discussionmentioning
confidence: 99%